Family Involvement: Sebuah Usaha Sinergi Orang Tua Dengan Gereja dalam Pelayanan Kaum Muda Di Era Pasca-Pandemi - Andreias, Tomo (Veritas : Jurnal Teologi dan Pelayanan, 2023)
Parents are called to nurture the faith of their children. However, it is ironic that many parents simply leave the responsibility of faith formation solely to the church. Such a reality was forced to change by the pandemic which conditioned parents to return home and caused the church to face its limitations in engaging with her congregation. This condition is then seen by the author as an opportunity to work on youth ministry with a family involvement strategy that leads to a synergy between parents and churches that carry out their roles appropriately. That is why, through this article, the author conducts a literature review and uses a descriptive-analytical method to provide a critical review of the pattern of youth faith formation that has been carried out so far and provides an overview of the impact of the pandemic on this pattern. After that, an exposition of Deuteronomy 6:4-21 is conducted to provide the biblical basis for family involvement where parents are actively involved in nurturing their children. Finally, the author offers some practical steps for family involvement strategies so that, in the post-pandemic era, youth ministry will have alternative and effective strategies to bring young people to know and glorify God.